The Role of the Let-7 microRNA Family as Biomarker Prognostic Indicator Against Breast Cancer (Journal of Pharmaceutical Negative Results, 2022)
Breast Cancer is considering the most common cancer in Iraq and the major cause of cancer related deaths among women Iraqi Cancer Registry and Ministry of Health, Republic of Iraq, and also Among women in Iraq, breast cancer is the most frequent type of cancer. Material AND Methods: This study was designed to focus on microRNAs expression in breast cancer, by Measuring the levels of circulating microRNAs in all samples by determining the fold expression of the detected microRNAs by RT qPCR. The study, involved 49 specimens were collected from the point of view of patients, particularly women with breast cancer, and blood samples were fully taken, in addition to taking samples in the same way as combining those healthy women (control group) 40 samples, and the work of extracting the RNA in the method of extracting the organic Chloroform of samples of the full blood of all samples in EDTA tubes. The study includes take information’s patient (age, city, history, and to adding information from histopathology examination). The results were referred to increase in gene expression to miRNA Iet-7 family (type b) in patient samples (BC females) compared with control group (healthy women) by q-RT-PCR also measured IL-8 levels by ELISA technique and the results were referred to raise in IL-8 levels of BC females for serum samples compared with control group (healthy women). The cut off value for miR-let-7 was > 11.18-fold change with low sensitivity (58.5 %), high specificity (97.5 %) and good accuracy (81.8 %). Therefore, can be used MiRNA Let-7 as biomarker predictors of diagnosis of breast cancer. Conclusion: The current study was concluded, significant over productions of all investigated parameters referred to increase in levels micro-RNA let-7 family (let-7 type-b) seems to have potential role in breast prognosis of cancer progression when compared with healthy people. This study has found that all the investigated parameters were associated with moderate to high grade carcinoma.